Transforming growth factor beta 1 level in differentiated thyroid tumors, metastases and blood plasma - N.Ya. Kobrynska; V.M. Pushkarev; N.I. Levchuk; O.I. Kovzun; I.I. Komisarenko; B.B. Guda; M.D. Tronko (Mìžnarodnij Endokrinologìčnij Žurnal)
Background. One of the most important tasks facing endocrine surgery is the determination of reliable markers of metastasis in the treatment of papillary thyroid carcinoma (PTC). Markers that can be determined at the stage of preoperative research are of particular value. Transforming growth factor β1 (TGF-β1) can be one of these markers. The aim of the study was to compare the levels of TGF-β1 in tissue samples of follicular adenoma, goiter, PTC, metastases, and conditionally normal tissue. Materials and methods. Postoperative samples of tissue and blood plasma obtained from the surgical department of the V.P. Komisarenko Institute of Endocrinology and Metabolism of NAMSU clinic were used for research. The amount of TGF-β1 was determined using enzyme immunoassay kits. Results. The level of TGF-β1 in the tissue of follicular adenoma and nodular goiter exceeded the levels in conditionally normal tissue by approximately 2 times. There was significant difference from conditionally normal tissue in РТС tissues without metastases. The concentration of TGF-β1 in the tumor tissue of РТС with metastases was higher than in the conditionally normal tissue by almost 5 times and by 3 times higher than in РТС tissues without metastases. It is important to note that the level of TGF-β1 in metastases was higher than in the adenoma and goiter tissue but did not differ from tumor tissue of РТС without metastases. In blood plasma of patients with PTC without metastases, the concentration of TGF-β1 significantly exceeded that in controls, but did not differ from patients with PTC and metastases. Conclusions. Our data indicate significant differences in the concentration of TGF-β1 between tumor tissues of PTC with and without metastasis. In blood plasma of patients with PTC without metastases, TGF-β1 level exceeded that in controls, but did not differ from patients with PTC and metastases.